Improving Labor Market Outcomes for Poor and Vulnerable Groups in Mongolia - Gassmann, Franziska; Francois, Daphne; Zardo Trindade, Lorena (World Bank, Washington, DC, 2016)
Mongolia has experienced strong economic growth and declining poverty in the past. With the implementation of the law on employment promotion in 2011, the Government of Mongolia provided the legal base for a set of employment promotion programs. By means of these programs, different vulnerable labor market groups are addressed, ranging from graduates to disabled, older workers, herders, and unskilled job seekers. The objective of the report is to describe and analyze labor market outcomes for different groups of the population in Mongolia, with a particular focus on poor and vulnerable households, and present a set of policy interventions to strengthen the labor market participation and integration of currently unemployed or inactive adults. The focus of the report is on supply side issues of the labor market. In order to better understand the mechanisms driving labor market outcomes, a prospective qualitative analysis is already planned to complement the present quantitative analysis. The report is structured as follows: section one gives introduction. Section two provides the country context in terms of economic and demographic developments and the characteristics of the Mongolian labor market. The empirical analysis is presented in section three. In section four the existing labor market policies in Mongolia are mapped and their challenges discussed. Finally, section five concludes and recommends a set of policy measures to further improve the labor market outcomes of poor and vulnerable groups.